Assessing the Nomological Network of the South African Personality Inventory With Psychological Traits - Hill, Carin; Nel, Jan Alewyn; de Beer, Leon T.; Fetvadjiev, Velichko H.; Stevens, Lyle I; Bruwer, Monique (Frontiers in Psychology, 2021)
The purpose of this study was to expand internal construct validity and equivalence research of the South African Personality Inventory (SAPI), as well as to investigate the nomological validity of the SAPI by examining its relationship with specific and relevant psychological outcomes. The internal and external validity of the SAPI was assessed within three separate samples (N = 936). Using the combined data from all three samples, Exploratory Structural Equation Modelling (ESEM) indicated that the six-factor SAPI model fit proved to be excellent. Measurement invariance analyses showed that the SAPI dimensions in the ESEM model were invariant across gender and race groups. Next, two separate studies explored the associations of the SAPI factors with relevant psychological outcomes. An ESEM-within-CFA (set ESEM) method was used to add the factors into a new input file to correlate them with variables that were not part of the initial ESEM model. Both models generated excellent fit. In Study 1, psychological well-being and cultural intelligence were correlated with the SAPI factors within a sample of students and working adults. All of the psychological well-being dimensions significantly correlated with the SAPI factors, while for cultural intelligence, the highest correlations were between Meta-cognition and Openness and Meta-cognition and Positive Social-Relational Disposition. In Study 2, work locus of control and trait anxiety was correlated with the SAPI factors within a sample of adults from the general South African workforce. Work Locus of Control correlated with most factors of the SAPI, but more prominently with Positive Social-Relational Disposition, while Neuroticism correlated strongly with trait anxiety. Finding an appropriate internal structure that measures personality without bias in a culturally diverse context is difficult. This study provided strong evidence that the SAPI meets the demanding requirements of personality measurement in this context and generated promising results to support the relevance of the SAPI factors.